Effects of phenolic compounds of fermented thai indigenous plants on oxidative stress in streptozotocin-induced diabetic rats - Chaiyasut C. (2014)
We investigated the effects of antioxidant activity of fermentation product (FP) of five Thai indigenous products on oxidative stress in Wistar rats with streptozotocin (STZ)-induced diabetes type II. The rats were fed with placebo and with the FP (2 and 6mL/kg body weight/day) for 6 weeks. Rutin, pyrogallol and gallic acid were main compounds found in the FP. Plasma glucose levels in diabetic rats receiving the higher dose of the FP increased less when compared to the diabetic control group as well as the group receiving the lower FP dose (13.1%, 29%, and 21.1), respectively. A significant dose-dependent decrease in plasma levels of thiobarbituric acid reactive substance (P <.05) was observed. In addition, the doses of 2 and 6mL FP/kg/day decreased the levels of erythrocyte ROS in diabetic rats during the experiment, but no difference was observed when compared to the untreated diabetic rat group. Results imply that FP decreased the diabetes-associated oxidative stress to a large extent through the inhibition of lipid peroxidation. The FP also improved the abnormal glucose metabolism slightly but the difference was not statistically significant. Thus, FP may be a potential therapeutic agent by reducing injury caused by oxidative stress associated with diabetes. Copyright 2011 Chaiyavat Chaiyasut et al.